Global burden of pneumoconiosis attributable to occupational particulate matter, gasses, and fumes from 1990~2021 and forecasting the future trends: a population-based study - Mao Qingsong; Ruijie Xiao; Wenqi Yang; Xinyi Wang; Yu-zhe Kong (Frontiers in Public Health)
BackgroundThis study aimed to quantify the global impact of pneumoconiosis resulting from occupational exposure to particulate matter, gasses, and fumes from 1990 to 2021, utilizing data from the Global Burden of Disease Study 2021.MethodThe analysis evaluated the global, regional, and national burden of pneumoconiosis attributable to workplace exposure to particulate matter, gasses, and fumes. It explored variations in disease impact across different demographics, including age and gender, and analyzed the relationship between disease burden and the Socio-Demographic Index (SDI). Furthermore, an ARIMA model was employed to forecast future trends of pneumoconiosis up to 2050.ResultThe year 2021 saw pneumoconiosis from occupational particulate matter, gasses, and fumes account for roughly 4,775 deaths and 117.80 thousand disability-adjusted life years (DALYs). Over the past three decades, there was a notable decline in the disease’s burden. The condition predominantly affected males and those aged above 60. Future projections suggest a decrease in mortality rates in low to middle SDI regions, while high SDI regions may experience an increase in ASMR. Additionally, both ASMR and ASDR are anticipated to rise globally. Nationally, the Czech Republic, France, and the United States are expected to show relatively higher mortality rates in 2030 and 2050. Countries like Kazakhstan, Egypt, Mongolia, and Peru are projected to experience elevated levels of ASMR, DALY rates, and ASDR.ConclusionThe findings underscore the urgent need for policymakers to create and improve targeted preventive strategies to reduce the incidence of pneumoconiosis among specific populations.